Treatment of Ventral Hip Luxation in a Puppy - BOZKAN, Z.; BULUT, B.; BELLEK, C. G. (Journal of the Hellenic Veterinary Medical Society, 2021)
A Three months of age, 4.5 kg, female mixed (cross) breed presented to our clinic with complaint of the left hind leg lameness. In the clinical, radiographic and ultrasonographic examination, ventral hip luxation was diagnosed. Based on the examination findings which indicated the case was chronic, surgical treatment was decided. Hip joint was exposed firstly by craniodorsal approach. Flattened and full acetabulum, fractured greater trochanter, ruptured gluteal muscle attachment and irreparably broken joint capsule were determined. Excision arthroplasty was performed by ventral approach. Greater Trochanter was attached to its position by an L shape Steinman pin using craniodorsal approach. Then, a drill hole was created on the greater trochanter, and a screw was inserted to dorsal acetabular rim. A synthetic suture passed through the hole was tied to the screw in a figure of eight mode. Postoperative antibiotics and anti-inflammatory drugs were used. Physiotherapy such as swimming and massage treatments was proposed following skin sutures removal. In the 4th week control postoperatively, the dog began to use the operated leg effectively despite the moderate quadriceps’ contracture. The contracture was mostly resolved 12th week by continuing physiotherapy.